(untitled) (International Journal of Economics Management and Social Science, 2026)
This study examines social budget allocation as a policy instrument for poverty alleviation in four ASEAN countries: Indonesia, the Philippines, Vietnam, and Thailand. From the perspective of Islamic Social Finance, social spending represents a redistributive mechanism aimed at improving social welfare and reducing poverty. This research also investigates the extent to which Islamic Governance, reflected in institutional quality through corruption control, transparency, and accountability, strengthens the effectiveness of social spending in reducing poverty. The study aims to analyze the empirical relationship between social budget allocation and poverty reduction while examining the moderating role of institutional governance. This study uses panel data from 2004–2023, selected purposively based on the characteristics of social development and governance in ASEAN-4 countries. Secondary data were obtained from the World Bank and analyzed using panel data regression. Based on the Lagrange Multiplier test, the Random Effect Model was selected as the most appropriate estimation model. The moderating role of institutional governance was examined using Moderated Regression Analysis. The results indicate that social spending significantly reduces poverty in ASEAN-4. However, its effectiveness depends on institutional governance quality. Low transparency and accountability weaken the positive impact of social spending. Strengthening governance is therefore essential to ensure effective poverty alleviation strategies.